Electrochemical fluorosulfonylation of alkenes to access vicinal fluorinated sulfones derivatives. (29th January 2022) - Zhao, Bin; Pan, Zichen; Zhu, Anqiao; Yue, Yanni; Ma, Mengtao; Xue, Fei
Abstract: Herein, we report a practical and efficient fluorosulfonylation of the various alkenes with sulfonyl radical sources (RSO2 NHNH2 ) and Et3 N·3HF as cost-effective fluorination reagents under mild conditions. Remarkably, this protocol features very green and sustainable conditions obviating the need of chemical oxidants and transition metal catalyst. A variety of substituents on both sulfonyl hydrazides and alkenes are tolerated to give vicinal fluorinated sulfones in moderate to excellent yields. Also, the synthetic utility of this transformation is further demonstrated by a gram-scale reaction and the late-stage functionalization of complex molecules. Graphical abstract: Image 1